Improvement of corrosion resistance of tin coated on titanium alloy for biomedical application - A., Shah; Siti Nurul Fasehah, .; Mas Ayu, Hassan; Rosdi, Daud; Che Ghani, Che Kob (IOP Publishing, 2021)
This work aims to study the effect of mechanical treatment technique on titanium coated with PVD for the enhancement of corrosion resistance for the biomedical implant. First, substrates were coated with TiN via PVD then applied the mechanical treatment through ultrasonic vibration. Results show that all coated samples treated with ultrasonic vibration improve the surface of the coated sample and produce a compact coating as compared with a substrate coated without mechanical treatment. The corrosion test evaluated by Potentiodynamic polarization and Electrochemical Impedance Spectroscopy indicated that all coated samples treated with mechanical treatment showed high corrosion resistance as compared with the untreated sample. It can be concluded that mechanical treatment which is a simple technic can be used as an alternative to improve the corrosion resistance thus reduce the implant and manufacturing cost for biomedical applications.